PENGARUH BAURAN PEMASARAN, PESTER POWER, dan HERITAGE TERHADAP KEPUTUSAN PEMBELIAN BISKUIT MEREK ROMA MALKIST - Tehubijuluw, Florentina K.; Sari, Desy Permata (Manajemen Bisnis Kompetensi, 2017)
AbstractAn outstanding marketing mix strategy is needed to assist the customers in buying decision-making process and finally will increase the organization sales and revenue. This study will analyze the effect of the variables of marketing mix (namely: product, price, promotion and place) combined with the pester power and heritage into the buying decision of Roma Malkist biscuit in Tangerang region. The non-probability sampling method is used in this study and 155 Roma Malkist biscuit consumers in Tangerang as the target respondents. All data will be analyzed using the multiple linear regression method. The result of the data analysis showed that product, price and heritage variables had significant effect in buying decision making. On the contrary, distribution, promotion and pester power variables didn’t have ssignificant effect into buying decision making. Keywords: marketing mix, pester power, heritage and buying decision-making.